Improving Bos Fund Accountability Through ARKAS, Internal Control and Strengthened by Transparency - Enika Diana Batubara; M. Nursidin; Dominggus Sijauta; Dini Ventiany; Tengku Hasan (Universitas Muhammadiyah Malang, 2025)
Purpose: This study aims to analyze the effect of ARKAS implementation and internal control on the accountability of BOS fund management in high schools, with financial transparency as a moderating variable.Methodology/approach: A quantitative associative approach was employed, using SEM-PLS analysis on data from 87 respondents, including principals, treasurers, and BOS operators from public and private high schools in Medan. Data were collected through a structured questionnaire using a Likert scale, and analyzed with SmartPLS 4.Findings: The results indicate that both ARKAS implementation and internal control significantly influence accountability. Financial transparency significantly moderates the relationship between ARKAS and accountability, but not the relationship between internal control and accountability.Practical implications: These findings highlight the importance of strengthening internal control and implementing digital systems in parallel with genuine financial transparency practices.Originality/value: This study contributes to the public accounting literature by examining the moderating role of transparency in the context of education finance and digital financial systems.